Otomatisasi Proses Online Stock Opname pada Aplikasi Inventaris Barang untuk Multi Lokasi Pergudangan - Laura Mahendratta Tjahjono; Adi Suryaputra Paramita (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The process of stock opname of goods in a business is something that must be done regularly to control the business assets. The stock opname process generally requires a lot of money and time, especially in businesses that have many branch locations. During the implementation of stock opname, sales transactions are usually stopped so that the stock does not change. As a result, the longer the time for this process is required, the greater the loss. In addition, extra costs are also incurred when the implementing manager is sent to each branch location where the stock opname will be carried out. Due to the high costs and losses incurred, this stock opname is usually only done a few times a year. On the other hand, the low frequency of stock opname has an impact on increasing business losses due to loss of assets that cannot be detected early. This study aims to increase the effectiveness of the stock opname process to minimize losses that occur during the stocktaking process or losses due to delays in handling the loss of goods assets. The results of this study indicate that the new system design allows the stock opname process to be carried out remotely without the presence of a manager and without stopping sales transactions, so as to reduce operational costs. The frequency of stock opname can also be carried out more frequently so that if there is a loss of assets, it can be immediately identified and action is taken to avoid high business losses. The result of software testing using the Blackbox Testing method shows that the application can run well and the result of User Acceptance Testing shows the acceptance of respondents at 87%, which means that respondents accept the solutions offered well.